2023
DOI: 10.3390/jcm12134538
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of VHL, PTEN, and BAP1 Mutations in Renal Tumors

Abstract: The genetic profiling of renal tumors has revealed genomic regions commonly affected by structural changes and a general genetic heterogeneity. The VHL, PTEN, and BAP1 genes are often mutated in renal tumors. The frequency and clinical relevance of these mutations in renal tumors are still being researched. In our study, we investigated VHL, PTEN, and BAP1 genes and the sequencing of 24 samples of patients with renal tumors, revealing that VHL was mutated at a noticeable frequency (25%). Six of the investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
(193 reference statements)
0
2
0
Order By: Relevance
“…Apart from VHL gene inactivation, other epigenetic genes also play a contributing role in ccRCC development, which mainly includes phosphatase and tensin homolog (PTEN) and breast cancer type-1 (BRCA-1)associated protein-1 (BAP1) [23]. The latest study by Szegedi et al confirmed that VHL or PTEN mutations may contribute to the development of human renal cancers [27].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from VHL gene inactivation, other epigenetic genes also play a contributing role in ccRCC development, which mainly includes phosphatase and tensin homolog (PTEN) and breast cancer type-1 (BRCA-1)associated protein-1 (BAP1) [23]. The latest study by Szegedi et al confirmed that VHL or PTEN mutations may contribute to the development of human renal cancers [27].…”
Section: Discussionmentioning
confidence: 99%
“…Clear cell renal cell carcinoma (ccRCC) accounts for 75% of all kidney cancer cases ( 3 ). Most patients with ccRCC harbor von Hippel–Lindau ( VHL ) gene abnormalities ( 4 ). The encoded VHL protein is an E3 ubiquitin ligase that targets hypoxia-inducible factors (HIFs) for degradation; the inactivation of VHL and the consequent dysregulation of HIF pathway signaling are major drivers of ccRCC growth and progression ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%